Transcriptome Analysis of Reticulated Platelets Reveals a Prothrombotic Profile - Bongiovanni, Dario; Santamaria, Gianluca; Klug, Melissa; Santovito, Donato; Felicetta, Arianna; Hristov, Michael; von Scheidt, Moritz; Aslani, Maria; Cibella, Javier; Weber, Christian; Moretti, Alessandra; Laugwitz, Karl-Ludwig; Peano, Clelia; Bernlochner, Isabell (Thrombosis and Haemostasis, 2019)
Reticulated platelets (RPs) are larger, hyperreactive platelets that contain significantly more ribonucleic acid (RNA) compared with mature platelets (MPs). High levels of RPs in peripheral blood are predictors of an insufficient response to dual antiplatelet therapy in cardiovascular patients and of adverse cardiovascular events. However, the mechanisms underlying these correlations remain widely unknown and the biology of RPs has not been investigated yet. Here, we compared for the first time the transcriptomic profiles of RPs and MPs isolated from peripheral blood of healthy donors. Total RNA sequencing revealed 1,744 differentially expressed genes (670 downregulated, 1,074 upregulated) in RPs compared with MPs. In particular, transcripts for the collagen receptor GP6, thromboxane receptor A2 (TBXA2R), thrombin receptor PAR4 (F2RL3), and adenosine triphosphate receptors P2RX1, ORAI2, and STIM1 (both involved in calcium signaling) were significantly upregulated in RPs, whereas several RNA regulators as the ribonuclease PARN, the RISC-component TNRC6A, and the splicing factor LUC7L3 were downregulated in RPs. Gene ontology analysis revealed an enrichment of relevant biological categories in RPs including platelet activation and blood coagulation. Gene Set Enrichment Analysis showed an overrepresentation of several platelet activation pathways like thrombin, thromboxane, and glycoprotein IIb/IIIa signaling in RPs. Small-RNA sequencing reported 9 micro-RNAs significantly downregulated in RPs with targets involved in platelet reactivity. Our data show for the first time an enrichment of several prothrombotic transcripts in RPs providing a first biological explanation for their hyperreactive phenotype.
Keywords: reticulated platelet; immature platelet; platelet transcriptome; platelet physiology